Nocardiosis: A two-center analysis of clinical characteristics - Wang, Lumin; Xu, Yijiao; Chen, Zhisheng; Jiang, Weiwen; Xiao, Xiong; Shen, Yun; Ye, Yanrong (Frontiers in Medicine, 2022)
Objective The objective of the present study was to describe and analyze the clinical characteristics of nocardiosis. Materials and methods We described and analyzed the clinical characteristics of nocardiosis cases from two centers over the past 5 years from the following aspects: age and sex, Nocardia species, sites of Nocardia infection, test specimens, detection methods, concurrent pathogens, symptoms, imaging features, co-conditions, drug susceptibility tests, antibiotic therapy/duration, outcomes, and follow-up. Results The median age of the 19 cases was 64 years, with an interquartile range (IQR) of 56–68 years. Eight cases (42.1%) were immunocompromised [those who had been on corticosteroid use (62.5%), those who had used immunosuppressants (50.0%), or those who had suffered from chronic nephrosis (37.5%) or diabetes mellitus (DM) (25.0%)]. The plethora of comorbidities of these cases included diabetes (10.5%), chronic kidney disease (CDK) (15.8%), chronic lung disease (36.8%), and rheumatic diseases (10.5%). Cough and expectoration (73.7%) was the most common symptom of nocardiosis. The respiratory tract (89.5%) was the most common site of the clinical disease. Nearly half (9 cases, 47.3%) of these patients had concurrent infections. The most common Nocardia isolation site was the respiratory tract (73.7%). All patients were given antibiotic therapies, out of whom as many as 63.6% of patients were treated with two concurrent antimicrobial agents, 15.8% of patients were treated under monotherapy and 21.1% of patients were treated with three or more concurrent antimicrobial agents. Conclusions An uncommon life-threatening infection, nocardiosis, affects those patients with structural lung disease or immunosuppression. Although nocardiosis is capable of progressing into a serious and metastatic disease, early recognition and prompt treatment usually result in successful outcomes benefitting the patient.